Grant Code Sanctions of Polri Members Who Have Disconnected The Court Binding Drug Abuse (Case Study Polres Cirebon) - Joseph Diko Reinol Panjaitan (Jurnal Daulat Hukum, 2018)
This study aims to identify and understand the sanctions in the Code of Conduct Police officers and efforts to the implementation of sanctions against Alleged offenders alleged to have violated the code of Professional Ethics of Police, in the form of deeds has committed the crime of Abuse of Narcotics kind Sabu-shabu and cases criminal has received the Decision of the Court Of Sumber country, with an excerpt of Decision No. 394 / Pid.Sus / 2017 / PN.Sbr. October 19, 2017, which states the defendant initials S, proven legally and convincingly guilty of committing the crime of abuse of Narcotics Group I For Yourself and sentenced to imprisonment for six (6) months. This research was conducted in Cirebon. To the authors conducted a study with the title "Provision of the Code sanctions Police Members Who Have Strength Disconnect Law Courts Stay In Drug Abuse". If a member of the National Police of an offense or crime, the police members will litigants and undergo a criminal justice process for members of the Indonesian National Police is generally done according to the law applicable in the general court.Keywords: Police; Narcotics; Police Professional Code of Conduct of Police.